PEMANFAATAN TURBIN VENTILATOR DAN SISTEM PENCAHAYAAN BARU UNTUK MENINGKATKAN KESELAMATAN DAN KESEHATAN KERJA (STUDI KASUS IKM RANDANG KACANG) - Riko Ervil; Silfa Yona (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Randang Kacang is Small and Medium scale industries engaged in food. This industry have a standard of production, to meet the needs of consumers. This  utilized manpower to expedite the process of production. The production process is carried out in the room that have higher temperature. And the production room that has not had a lighting system, workers can lead to carelessness causes accidents, so that workers are not comfortable in working. Therefore we need an increase in Occupational Health and Safety. So workers can work comfortably, healthy and safe during the production process.  In this researched  need to perform the installation of the turbine ventilator, aiming to stabilize room temperature in the production room, according to the Indonesian National Standard  (SNI). Including to  design of artificial lighting systems. Utilized TL bulbs (flourescent) in some point in the production process rooms to avoid the worker  accidents. Installation of turbine ventilator performed at the top of the roof. At the top of the roof installed 2 turbine ventilator which has a diameter of 60 cm. Turbine ventilator can absorb 200% more air temperature. To reduce lack of lightening sistems utilized 18 watt Philips TL light bulbs (fluorescent) in 28 points according to SNI.  Keyword: Accident,Turbine Ventilator, SNI, Lighting Systems